Evolution of the Mass Loss Rate During Atmospheric and Pressurized Slow Pyrolysis of Wheat Straw in a Bench-Scale Reactor - Greco, Gianluca; Manyá, Joan J.; Gonzaléz, Belén; Videgain, María (Jornada de Jóvenes Investigadores del I3A, 2018)
A deep study focused on the significant effect of the absolute pressure on the yield of produced gas during the slow pyrolysis of biomass was carried out. In addition, the evolution of the mass loss rate linked to the pyrolysis process was also analyzed.